A battery

CN122907853APending Publication Date: 2026-10-13ZHUHAI COSMX BATTERY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611193336.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-06
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0006]为了改善现有技术中含硅碳叠片式电池沿宽度方向的侧边在机械冲击下易发生短路的问题,本发明提供了一种电池

Benefits of technology

(1)本发明通过将叠片式电极组件中负极片上下层隔膜在第一方向上超出负极片的第一部加热粘接形成第一复合区,形成隔膜包覆负极片侧边端面的结构,从而第一复合区对负极片边缘形成了物理约束,增强了负极活性层沿电池宽度方向(第一方向)的边缘与负极集流体的界面结合性,减少了负极活性层的滑移和起翘,减少甚至避免了隔膜刺穿;同时,第一复合区增强了隔膜整体的耐冲击能力,使不同极片层处的隔膜同时参与冲击应力的缓冲,进一步降低了负极活性层相对负极集流体的滑移风险,减少甚至避免了隔膜刺穿,从而叠片式电池耐侧边机械冲击的性能得到有效提升,内短路风险降低,电池安全性提升。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122907853A_ABST
    Figure CN122907853A_ABST
Patent Text Reader

Abstract

The application provides a battery. The battery of the application comprises a laminated electrode assembly, wherein a negative active layer of a negative electrode sheet comprises silicon-carbon particles, and a negative current collector comprises a copper foil with a tensile strength of 300-700 MPa and an elongation of 3%-15%; the electrode assembly comprises a first side surface and a second side surface oppositely arranged along a first direction, and in the first direction, a separator comprises a first part and a second part beyond the negative electrode sheet, the first part is located on a side close to the first side surface, and the second part is located on a side away from the first side surface, and the first part comprises a first composite area formed by adhesion of at least two first parts on opposite sides of a single negative electrode sheet in a second direction. The application can improve the side mechanical impact resistance of the laminated battery, reduce the risk of internal short circuit, and improve the safety of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery technology, and more specifically to a battery. Background Technology

[0002] With the increasing demands for battery energy density in consumer electronics, power tools, and drones, silicon-carbon anode materials have become an important development direction for high-energy-density lithium-ion batteries due to their higher theoretical specific capacity than traditional graphite anodes.

[0003] However, silicon-carbon materials have a large volume change rate during charging and discharging, and high stress is generated inside the negative electrode during cycling. Especially in the edge area of ​​the negative electrode, the interface between the negative electrode active layer and the negative current collector is in a high stress state. When the side of the stacked battery containing silicon-carbon negative electrode material is subjected to mechanical impact, the impact stress will be transmitted into the cell, which can easily cause the negative electrode active layer to puncture the separator, causing internal short circuit, or even fire or explosion.

[0004] Therefore, it is very important to improve the impact resistance of the sides of stacked batteries containing silicon-carbon materials. Summary of the Invention

[0005] Research has revealed that stacked solar cells containing silicon-carbon materials are more prone to internal short circuits along their width when subjected to mechanical impact. This is mainly due to two factors: Firstly, the negative electrode active layer is under higher stress at the edge region along the width of the cell, weakening the interfacial bonding strength between the edge of the negative electrode active layer and the negative electrode current collector. Under mechanical impact, the negative electrode active layer is prone to slippage and warping, and the end of the negative electrode active layer is easily punctured by the separator. Secondly, when the negative electrode active layer contains a high content of silicon-carbon material, the volume change rate increases, exacerbating the stress at the edge of the negative electrode sheet, reducing the interfacial bonding strength between the edge of the negative electrode active layer and the negative electrode current collector, and reducing the adhesion between silicon-carbon particles, increasing the risk of powder shedding, and increasing the number of particles protruding from the surface of the active layer, thus increasing the risk of separator puncture. On the other hand, the edge of the negative electrode current collector along the width of the battery is prone to cutting the separator under mechanical impact. After the negative electrode active layer slips and lifts, the buffer between the current collector and the separator is missing. The edge of the negative electrode current collector is also prone to breakage when subjected to mechanical impact, forming a sharp fracture, which further increases the risk of puncturing the separator and causing an internal short circuit.

[0006] To address the problem of short circuits occurring along the width-direction sides of existing silicon-carbon laminated batteries under mechanical impact, this invention provides a battery. This invention improves the resistance to side mechanical impacts of laminated batteries, reduces the risk of internal short circuits, and enhances battery safety.

[0007] To achieve the above objectives, the present invention provides a battery comprising a stacked electrode assembly, the electrode assembly comprising a positive electrode, a separator, and a negative electrode, the negative electrode comprising a negative current collector and a negative active layer located on at least one surface of the negative current collector, the negative active layer comprising a negative active material comprising silicon-carbon particles, the negative current collector comprising copper foil, the copper foil having a tensile strength of 300 MPa-700 MPa and an elongation of 3%-15%; The electrode assembly includes a first side surface and a second side surface disposed opposite to each other along a first direction. In the first direction, the separator includes a first portion and a second portion extending beyond the negative electrode sheet. The first portion is located on the side closer to the first side surface, and the second portion is located on the side away from the first side surface. The first portion includes a first composite region, which is formed by bonding two first portions located on opposite sides of a single negative electrode sheet in a second direction.

[0008] By employing the above technical solution, the present invention has at least the following advantages compared with the prior art: (1) The present invention forms a first composite region by heating and bonding the first part of the upper and lower layers of the separator in the negative electrode assembly that extends beyond the negative electrode in the first direction, thereby forming a structure in which the separator covers the side end face of the negative electrode. Thus, the first composite region forms a physical constraint on the edge of the negative electrode, which enhances the interfacial bonding between the edge of the negative electrode active layer along the width direction (first direction) of the battery and the negative electrode current collector, reduces the slippage and warping of the negative electrode active layer, and reduces or even avoids separator puncture. At the same time, the first composite region enhances the overall impact resistance of the separator, so that the separator at different electrode layers participates in the buffering of impact stress at the same time, further reducing the risk of slippage of the negative electrode active layer relative to the negative electrode current collector, reducing or even avoiding separator puncture. Thus, the performance of the stacked battery against side mechanical impact is effectively improved, the risk of internal short circuit is reduced, and the battery safety is improved.

[0009] (2) By controlling the tensile strength of the copper foil of the negative electrode current collector to 300MPa-700MPa and the elongation to 3%-15%, when the impact energy is transferred to the side of the negative electrode sheet along the width direction of the battery (first direction), the copper foil can undergo appropriate plastic deformation, making the edge shape more rounded, reducing the cutting effect on the separator. At the same time, the high tensile strength can prevent edge breakage, reduce the risk of internal short circuit caused by the negative electrode current collector piercing the separator, and further improve the safety of the stacked battery side when subjected to mechanical impact.

[0010] Other features and advantages of the present invention will be described in detail in the following detailed description section.

[0011] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein. Attached Figure Description

[0012] Figure 1 The image shown is a three-dimensional schematic diagram of a stacked electrode assembly in the prior art.

[0013] Figure 2 The figure shown is a three-dimensional schematic diagram of the stacked electrode assembly of the present invention.

[0014] Figure 3 The image shown is one of the cross-sectional schematic diagrams of the stacked electrode assembly of the present invention.

[0015] Figure 4 The image shown is a second cross-sectional schematic diagram of the stacked electrode assembly of the present invention.

[0016] Figure 5 The diagram shown is a surface schematic of the separator and negative electrode sheet of the present invention. Detailed Implementation

[0017] The following provides a detailed description of specific embodiments of the present invention. It should be understood that the specific embodiments described herein are for illustrative and explanatory purposes only and are not intended to limit the invention. Unless otherwise specified herein, data ranges include endpoints.

[0018] It should be noted that the numerical designations such as "first" and "second" in this invention are only used to distinguish different substances or methods of use, and do not represent a difference in order.

[0019] While the presence of silicon-carbon materials in batteries can increase their energy density, research has revealed that the volumetric properties of silicon-carbon materials cause issues along the width of stacked batteries containing these materials (e.g., ...). Figure 1 When subjected to mechanical impact, the sides A and / or B along the first direction X are prone to internal short circuits.

[0020] To improve the safety of the sidewalls of silicon-carbon composite cells under mechanical impact along their width, this invention provides a battery comprising a stacked electrode assembly. The electrode assembly includes a positive electrode, a separator, and a negative electrode. The negative electrode includes a negative current collector and a negative active layer located on at least one side surface of the negative current collector. The negative active layer includes a negative active material comprising silicon-carbon particles. The negative current collector includes copper foil. The tensile strength of the copper foil is 300 MPa-700 MPa, for example, 300 MPa, 350 MPa, 400 MPa, 450 MPa, 500 MPa, 550 MPa, 600 MPa, 650 MPa, or 700 MPa. The elongation of the copper foil is 3%-15%, for example, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, or 15%. The electrode assembly includes a first side surface and a second side surface disposed opposite to each other along a first direction. In the first direction, the separator includes a first portion and a second portion extending beyond the negative electrode sheet. The first portion is located on the side closer to the first side surface, and the second portion is located on the side away from the first side surface. The first portion includes a first composite region, which is formed by bonding two first portions located on opposite sides of a single negative electrode sheet in a second direction.

[0021] In this invention, such as Figure 1 and Figure 2 As shown, the battery includes a stacked electrode assembly 1. The width direction of the electrode assembly is a first direction X, which is perpendicular to the tab extension direction in the horizontal direction. The thickness direction of the electrode assembly is a second direction Y. The height direction of the electrode assembly is a third direction Z, which is parallel to the tab extension direction.

[0022] In this invention, such as Figure 3 As shown, the battery includes a stacked electrode assembly 1, which includes a positive electrode 11, a separator 12 and a negative electrode 13. The negative electrode 13 includes a negative current collector 131 and a negative active layer 132 located on at least one side of the surface of the negative current collector 131.

[0023] In this invention, such as Figure 3As shown, the electrode assembly 1 includes a first side surface 14 and a second side surface 15 disposed opposite to each other along a first direction X. In the first direction X, the diaphragm 12 includes a first portion 121 and a second portion 122 extending beyond the negative electrode sheet. The first portion 121 is located on the side close to the first side surface 14, and the second portion 122 is located on the side away from the first side surface 14. The first portion 121 includes a first composite region 1211, which is formed by bonding together at least two first portions 121 located on opposite sides of a single negative electrode sheet 13 in the second direction Y.

[0024] In this invention, in a stacked electrode assembly, the upper and lower separators of the negative electrode extend beyond the first portion of the negative electrode in a first direction, including a first composite region formed by bonding, thereby forming a structure in which the separator covers the side end of the negative electrode in the first direction (e.g., Figure 2 and Figure 3 As shown, the first composite region effectively constrains the side edge of the negative electrode active layer in the first direction, further enhancing the interfacial bonding between the side edge of the negative electrode active layer and the negative electrode current collector, reducing the slippage and warping of the negative electrode active layer, thereby reducing the risk of the negative electrode active layer puncturing the separator. At the same time, the first composite region enhances the overall impact resistance of the separator, allowing the separator at different electrode layers to participate in the buffering of impact stress simultaneously, further reducing the risk of slippage of the negative electrode active layer relative to the negative electrode current collector, thereby improving the side mechanical impact resistance of the stacked battery, reducing the risk of internal short circuit in the stacked battery, and improving battery safety.

[0025] To further reduce or even avoid the formation of sharp fractures at the two sides of the negative electrode current collector along the width direction (first direction) of the battery under mechanical impact, this invention also controls the tensile strength of the copper foil of the negative electrode current collector to be 300 MPa-700 MPa and the elongation to be 3%-15%. When the impact energy is transferred to the side edge of the negative electrode sheet, if the copper foil simultaneously meets the above-mentioned tensile strength and elongation range, the negative electrode current collector can undergo a certain degree of plastic deformation under mechanical impact, making the edge morphology of the negative electrode current collector in the first direction tend to be smooth, reducing the cutting effect of the negative electrode current collector on the separator. At the same time, the high tensile strength ensures that the edge of the negative electrode current collector is not easy to break under impact, thereby reducing the risk of internal short circuit caused by the edge of the negative electrode current collector piercing the separator, and further improving the safety of the battery side when subjected to mechanical impact. When the elongation of the copper foil is too low (e.g., below 3%), the edge of the negative electrode current collector lacks the ability to undergo plastic deformation under impact, making it prone to sharp fractures and increasing the risk of puncturing the separator. When the elongation is too high (e.g., above 15%), the copper foil's ability to adapt to and constrain the electrochemical expansion of the silicon-carbon material is insufficient, leading to deterioration in battery cycle performance. When the tensile strength of the copper foil is too low (e.g., below 300 MPa), the foil's insufficient rigidity easily causes processing deformation. Conversely, when the tensile strength is too high (e.g., above 700 MPa), the copper foil's hardness increases, and its plasticity drops sharply. Under lateral impact, the risk of brittle fracture of the negative electrode current collector increases dramatically, increasing the risk of separator puncture and internal short circuit, both of which are detrimental to battery safety and cycle life.

[0026] In this invention, the first composite region is formed by heating and bonding the first portions of two separators on opposite sides of the negative electrode sheet at a temperature of 120℃-160℃ (e.g., 120℃, 125℃, 130℃, 135℃, 140℃, 145℃, 150℃, 155℃, or 160℃) for a heating time of 1s-8s (e.g., 1s, 2s, 3s, 4s, 5s, 6s, 7s, or 8s). When the heating temperature is between 120℃ and 160℃, the separator can be fully thermally melted and form a stable structure covering the end face of the negative electrode sheet, enhancing the constraint on the edge region of the negative electrode active layer in the first direction, enhancing the interfacial bonding between the edge of the negative electrode active layer and the negative electrode current collector, reducing the slippage of the negative electrode active layer, reducing the risk of separator puncture, and simultaneously preventing the first The rigidity of the composite region is excessively enhanced, while maintaining appropriate flexibility to buffer impact stress and slow down the transmission of stress from the edge to the inside of the negative electrode sheet. This further reduces the slippage of the negative electrode active layer relative to the negative electrode current collector and lowers the risk of separator puncture. However, when the heating temperature is too low (e.g., below 120°C), the separator is not sufficiently melted, and the bonding strength between the separator on the upper and lower sides of the negative electrode sheet is insufficient. The structure of the first composite region covering the end face of the negative electrode sheet is prone to separation and failure under impact, which cannot further strengthen the interfacial bonding between the edge area of ​​the negative electrode active layer and the negative electrode current collector and improve the side impact resistance of the stacked battery. When the heating temperature is too high (e.g., above 160°C), the separator melts excessively, and the first composite region shrinks severely or forms a hard and brittle edge, reducing the impact toughness of the first composite region and increasing the risk of separator puncture and internal short circuit. When the heating time is too short (e.g., less than 1 second), the heat transfer is insufficient and the separator is not completely melted, which will also lead to insufficient separator bonding strength. The structure of the first composite region covering the end face of the negative electrode sheet is prone to failure, and it is impossible to further improve the interface bonding between the edge area of ​​the negative electrode active layer and the negative electrode current collector and improve the side impact resistance of the stacked battery. When the heating time is too long (e.g., more than 8 seconds), overheating will cause the first composite region of the separator to become brittle, reduce the impact toughness of the first composite region, and increase the risk of separator puncture and internal short circuit. In addition, the increase in heating time will also lead to a decrease in production efficiency.

[0027] In this invention, the elongation and tensile strength of the copper foil are controlled by adjusting the electrolysis process parameters or heat treatment conditions.

[0028] In this invention, the elongation of the copper foil refers to the elongation of the copper foil along its length (i.e.,...). Figure 3The elongation in the first direction shown in the figure. In this invention, the elongation and tensile strength of the copper foil can be obtained by conventional methods in the art. For example, after discharging the battery to 0% SOC, the negative electrode sheet is disassembled and the negative electrode active layer on the surface of the negative electrode sheet is removed to obtain the negative electrode current collector copper foil, or the prepared negative electrode current collector copper foil is directly taken and tested at 20℃-25℃ according to the test method of GB / T228.1-2021 with a gauge length of 50mm and a tensile speed of 50mm / min to obtain the tensile strength and elongation of the copper foil.

[0029] In this invention, the portion of the separator extending beyond the negative electrode sheet includes a first composite region, and the copper foil exhibits a tensile strength of 300MPa-700MPa and an elongation of 3%-15%, which, compared to existing technologies, improves the safety of the stacked battery side when subjected to mechanical impact. To further enhance the effect, one or more of the technical features can be further optimized.

[0030] In some embodiments, the elongation of the copper foil is 10%-13%. Controlling the elongation of the copper foil to 10%-13% can further enhance the plastic deformation capability of the copper foil, further reduce the cutting effect of the negative electrode current collector on the separator under mechanical impact, further reduce the risk of internal short circuit caused by the edge of the negative electrode current collector piercing the separator, and improve the safety of the battery.

[0031] In some embodiments, the silicon-carbon particles account for 20%-80% of the weight of the negative electrode active layer, for example, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75% or 80%.

[0032] By controlling the weight percentage of silicon-carbon particles in the negative electrode active layer to 20%-80%, it is possible to maintain a suitable stress state along the side edges of the negative electrode active layer along the width direction of the battery while ensuring volumetric energy density. This avoids excessive volume changes in the negative electrode active layer, reduces or even eliminates the degradation of the interfacial bonding strength between the side edges of the negative electrode active layer and the negative electrode current collector, lowers the risk of slippage, and ensures the adhesion within the negative electrode active layer, reducing powder shedding and the generation of particles protruding from the surface of the active layer. This further reduces the risk of separator puncture and improves the safety of the battery side when subjected to mechanical impact. When the weight percentage of silicon-carbon particles is too low (e.g., below 20%), the improvement in battery volumetric energy density is limited. When the weight percentage of silicon-carbon particles is too high (e.g., above 80%), the volume change of the negative electrode active layer is too large, which may lead to aggravated degradation of the interfacial bonding between the side edges of the negative electrode active layer and the negative electrode current collector. Under mechanical impact, the negative electrode active layer is more likely to slip and puncture the separator, increasing the risk of internal short circuit.

[0033] In some embodiments, the silicon-carbon particles account for 40%-80% of the weight of the negative electrode active layer.

[0034] In some embodiments, in the first direction X, the width of the first composite region (e.g. Figure 5 a in 1 The width (as shown) ranges from 0.8mm to 2.5mm, for example, 0.8mm, 0.9mm, 1mm, 1.1mm, 1.2mm, 1.3mm, 1.4mm, 1.5mm, 1.6mm, 1.7mm, 1.8mm, 1.9mm, 2mm, 2.1mm, 2.2mm, 2.3mm, 2.4mm, or 2.5mm. The first composite region has suitable bonding strength, which helps to enhance the physical constraint of the first composite region on the edge region of the negative electrode active layer, strengthen the interfacial bonding between the edge region of the negative electrode active layer and the negative electrode current collector, and reduce the risk of slippage of the negative electrode active layer relative to the negative electrode current collector when the side is subjected to mechanical impact, further reducing the risk of separator puncture. Simultaneously, the first composite region with the aforementioned width can also provide sufficient buffer for the side of the stacked electrode assembly, reducing the transmission of impact stress to the interior of the negative electrode sheet, further improving the mechanical impact resistance of the stacked battery side, thereby further reducing or even avoiding internal short circuits when the side of the stacked battery is subjected to mechanical impact, and improving its safety.

[0035] When the width of the first composite region in the first direction X is too small (e.g., less than 0.8 mm), the constraint force of the first composite region is insufficient, making it difficult to further constrain the edge area of ​​the negative electrode active layer with high stress, improve the interface bonding between the negative electrode active layer and the negative electrode current collector, and the negative electrode active layer is prone to slipping relative to the negative electrode current collector under mechanical impact, causing it to lift and puncture the separator. In addition, the first composite region does not cover the side of the stacked electrode assembly in the first direction enough, and cannot further improve the ability of the first composite region to buffer mechanical impact. When the side of the stacked battery is subjected to mechanical impact, internal short circuit is prone to occur, reducing the safety of the side of the stacked battery under mechanical impact. When the width of the first composite region is too large (e.g., greater than 2.5 mm), the first composite region will occupy part of the negative electrode space, which will have a certain impact on the volumetric energy density of the battery.

[0036] In some embodiments, such as Figure 5 As shown, the first composite region 1211 includes a first side 12111 close to the negative electrode 13. In the first direction X, the distance between the first side 12111 and the negative electrode 13 (e.g., ...) Figure 5 b 1The distance between the first edge and the negative electrode sheet is greater than or equal to 0.2 mm, for example, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1 mm, 1.2 mm, 1.5 mm, 2.0 mm, 2.5 mm, or 3 mm. Controlling the distance between the first edge and the negative electrode sheet to greater than or equal to 0.2 mm ensures that the first composite area is close to the negative electrode sheet, providing sufficient buffering when the side of the stacked battery is subjected to mechanical impact, further reducing or even avoiding stress transmission from the edge to the interior, reducing slippage and warping of the negative electrode active layer, further reducing the risk of separator puncture, and improving battery safety. On the other hand, leaving an appropriate gap between the first edge of the first composite area and the negative electrode sheet prevents the heating die from getting too close to the negative electrode active coating during heat treatment, which could damage the coating structure and affect the subsequent cycle performance of the battery.

[0037] In some embodiments, such as Figure 3 As shown, the negative electrode 13 has a first end face 133 and a second end face 134 at both ends in the first direction X. The first end face 133 is located on one side of the first side surface 14, and the second end face 134 is located on one side of the second side surface 15. The positive electrode 11 has a third end face 113 and a fourth end face 114 at both ends in the first direction X. The third end face 113 is located on one side of the first side surface 14, and the fourth end face 114 is located on one side of the second side surface 15. The second part at least covers a portion of the second end face of the negative electrode, and / or, the second part at least covers a portion of the fourth end face of the positive electrode. According to a specific embodiment, as follows... Figure 3 As shown, the second part 122 at least covers a portion of the fourth end face 114 of the positive electrode 11. According to one embodiment, the second part at least covers a portion of the second end face of the negative electrode. According to another embodiment, the second part at least covers a portion of the second end face of the negative electrode, and the second part at least covers a portion of the fourth end face of the positive electrode.

[0038] In some embodiments, such as Figure 4 As shown, the second part 122 includes a second composite region 1221, which is formed by bonding at least two second parts 122 located in the second direction Y.

[0039] According to one specific embodiment, the first part includes a first composite region, which is formed by bonding two first parts located on opposite sides of a single negative electrode sheet in a second direction, and the second part includes a second composite region, which is formed by bonding two second parts located in the second direction.

[0040] In some embodiments, such as Figure 5As shown, in the first direction X, the width of the second composite region (e.g.) Figure 5 a in 2 (As shown) the thickness ranges from 0.8mm to 2.5mm, for example, 0.8mm, 0.9mm, 1mm, 1.1mm, 1.2mm, 1.3mm, 1.4mm, 1.5mm, 1.6mm, 1.7mm, 1.8mm, 1.9mm, 2mm, 2.1mm, 2.2mm, 2.3mm, 2.4mm, or 2.5mm.

[0041] In some embodiments, such as Figure 5 As shown, the second composite region 1221 includes a second side 12211 near the negative electrode 13. In the first direction X, the distance between the second side 12211 and the negative electrode 13 (e.g., ...) Figure 5 b 2 (as shown) greater than or equal to 0.2 mm, for example, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1 mm, 1.2 mm, 1.5 mm, 2.0 mm, 2.5 mm or 3 mm.

[0042] In some embodiments, such as Figure 3 As shown, on the first side surface 14, the number of the first end faces 133 corresponding to the first composite region 121 is N. 1 (For example, 10, 15, 20, 25, 30, 35, 40, 45, or 50), the total number of the first end faces 133 is M. 1 (For example, 10, 15, 20, 25, 30, 35, 40, 45, or 50), N 1 and M 1 Satisfying 20% ​​≤ (N) 1 / M 1 ) × 100% ≤ 100% (e.g., 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, or 100%). For example, as... Figure 3 As shown, on the first side surface 14, the number N of the first end faces 133 corresponding to the first composite region 121 is... 1 The total number of the first end face 133 is M, which is 3. 1 For 3, N 1 and M 1 The result satisfies (3 / 3) × 100% = 100%.

[0043] When N 1 and M 1 Satisfying 20% ​​≤ (N) 1 / M1 When the percentage of first composite regions (×100%) is less than or equal to 100%, it ensures that the first end face of the negative electrode edge is covered by the first composite region, thus providing a sufficient amount of rigid first composite region on the side of the stacked electrode assembly. This further reduces the transfer of impact energy into the electrode assembly, lowers the risk of short circuit due to separator puncture, and improves the safety of the stacked battery side under mechanical impact. When the percentage is less than 20%, the number of first composite regions is insufficient, and under mechanical impact, the negative electrode active layer may still slip, leading to separator puncture and short circuit between the positive and negative electrodes, still posing a short circuit risk.

[0044] In some embodiments, N 1 and M 1 Satisfying 80% ≤ (N) 1 / M 1 )×100%≤100%. When N 1 and M 1 Satisfying 80% ≤ (N) 1 / M 1 If 100% ≤ 100%, it means that the number of the first end face of the negative electrode corresponding to the first composite region accounts for a large proportion of the total number of the first end face of the negative electrode. Most of the first end faces of the negative electrode in the stacked electrode assembly are covered by the first composite region, which helps to maintain the effective constraint of the first composite region on the edge of the negative electrode, further reducing the risk of internal short circuit caused by the slippage of the negative electrode active layer and edge lifting, and improving the safety of the battery side.

[0045] In some embodiments, such as Figure 4 As shown, the electrode assembly 1 includes a first surface 16 and a second surface 17 disposed opposite to each other along the second direction Y. Along the second direction Y, the first composite region 1211 is close to the first surface 16, and / or, along the second direction Y, the first composite region 1211 is close to the second surface 17.

[0046] When the side of a stacked battery is subjected to mechanical impact, the impact stress is first applied to the outer surface of the electrode assembly. This invention brings the first composite region with increased rigidity closer to the first surface and / or the second surface, which can more directly buffer and dissipate some of the impact energy, reduce the transmission of impact energy to the inside of the electrode assembly, further reduce the risk of short circuit due to separator puncture, and improve the safety of the side of the stacked battery when subjected to mechanical impact. Moreover, the negative electrode sheet near the outer surface of the electrode assembly is least constrained by the interlayer, and the bonding force between the edge region of the negative electrode active layer along the first direction and the negative electrode current collector is the weakest. It is also most prone to slippage and warping when subjected to mechanical impact, puncturing the separator. By controlling the first composite region to be close to the first surface and / or the second surface, the separators on the upper and lower sides of the negative electrode sheet near the first surface and / or the second surface are bonded to form the first composite region. The first composite region forms a physical constraint at the edge of the negative electrode sheet, which helps to reduce the slippage and warping of the negative electrode sheet near the outer surface, further reducing the risk of separator puncture and ensuring the safety of the side mechanical impact.

[0047] According to one specific embodiment, along the second direction, the first composite region is close to the first surface, and / or, along the second direction, the first composite region is close to the second surface, and on the first side surface, the number of first end faces corresponding to the first composite region is N. 1 The total number of the first end faces is M. 1 N 1 and M 1 Satisfying 20% ​​≤ (N) 1 / M 1 ()×100%≤100%. For example, such as Figure 4 As shown, along the second direction Y, the first composite region 1211 is close to the first surface 16, and the first composite region 1211 is close to the second surface 17. On the first side surface 14, the number N of the first end faces 133 corresponding to the first composite region 1211 is... 1 The total number of the first end face 133 is M, which is 2. 1 For 3, N 1 and M 1 The result satisfies (2 / 3) × 100% = 67%.

[0048] In some embodiments, such as Figure 4 As shown, on the second side surface 15, the number of second end faces 134 corresponding to the second composite region is N. 2 (For example, 10, 15, 20, 25, 30, 35, 40, 45, or 50), the total number of the second end faces 134 is M. 2 (For example, 10, 15, 20, 25, 30, 35, 40, 45, or 50), N 2 and M 2 Satisfying 20% ​​≤ (N)2 / M 2 )×100%≤100%, for example, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, or 100%. Similarly, it can further ensure that a sufficient amount of rigid second composite zone is provided for the side of the stacked electrode assembly, further reduce the transfer of impact energy to the inside of the electrode assembly, reduce the risk of short circuit due to separator puncture, and improve the safety of the side of the stacked battery when subjected to mechanical impact.

[0049] In some embodiments, N 2 and M 2 Satisfying 80% ≤ (N) 2 / M 2 )×100%≤100%, when N 2 and M 2 Satisfying 80% ≤ (N) 2 / M 2 If 100% ≤ 100%, it means that the number of the second end face of the negative electrode corresponding to the second composite region accounts for a large proportion of the total number of the second end face of the negative electrode. Most of the second end face of the negative electrode in the stacked electrode assembly is covered by the second composite region, which helps to maintain the effective constraint of the second composite region on the edge of the negative electrode, further reducing the risk of internal short circuit caused by the slippage of the negative electrode active layer and edge lifting, and improving the safety of the battery side.

[0050] In some embodiments, the electrode assembly includes a first surface and a second surface disposed opposite to each other along the second direction, wherein the second composite region is close to the first surface along the second direction, and / or, the second composite region is close to the second surface along the second direction. Similarly, controlling the second composite region to be close to the outer surface of the electrode assembly can more directly buffer and dissipate some of the impact energy, reduce the transmission of impact energy to the interior of the electrode assembly, and at the same time form a physical constraint on the edge of the negative electrode near the outer surface, which helps to reduce the slippage and warping of the negative electrode near the outer surface, further reducing the risk of separator puncture and improving the safety of the side of the stacked battery when subjected to mechanical impact.

[0051] According to one specific embodiment, along the second direction, the second composite region is close to the first surface, and / or, along the second direction, the second composite region is close to the second surface, and on the second side surface, the number of second end faces corresponding to the second composite region is N. 2 The total number of the second end faces is M. 2 N 2 and M 2 Satisfying 20% ​​≤ (N) 2 / M 2)×100%≤100%.

[0052] In some embodiments, such as Figure 4 and Figure 5 As shown, the negative electrode 13 has a first end face 133 and a second end face 134 at both ends in the first direction X. The first end face 133 is located on one side of the first side surface 14, and the second end face 134 is located on one side of the second side surface 15. The first composite region 1211 includes a third side 12112 away from the negative electrode 13. The first part 121 is peeled off from the third side 12112 until the first part 121 is peeled off from the first end face 133. The average peeling force required is 8N / m-18N / m, for example, 8N / m, 9N / m, 10N / m, 11N / m, 12N / m, 13N / m, 14N / m, 15N / m, 16N / m, 17N / m or 18N / m. Controlling the peeling force to 8N / m-18N / m ensures sufficient bonding strength between the two separators in the first composite region and between the separator and the first end face of the negative electrode sheet. This provides effective constraint and coverage for the edge region of the negative electrode active layer along the first direction, enhances the interfacial bonding strength between the edge region of the negative electrode active layer and the negative electrode current collector, further reduces or even avoids slippage or lifting of the negative electrode active layer that may puncture the separator during mechanical impact, and improves the safety of the battery. When the peel force is too low, for example, below 8 N / m, under mechanical impact conditions, the two separators in the first composite zone may detach, or the separator may detach from the first end face of the negative electrode sheet. The negative electrode active layer may still slip and puncture the separator. When the peel force is too high, for example, above 18 N / m, it means that a higher heating temperature or a longer heating time is required to form the first composite zone. This leads to excessive hardening of the first composite zone of the separator, which will reduce the buffer toughness of the first composite zone and make it unable to further slow down the transmission of impact stress to the inside of the negative electrode sheet. This will worsen the adhesion between the negative electrode sheet and the negative electrode current collector, exacerbate the lifting and slippage of the negative electrode active layer, increase the risk of separator puncture, and is not conducive to further improving the safety of the battery side when subjected to mechanical impact.

[0053] In some embodiments, such as Figure 5As shown, the second composite region 1221 includes a fourth side 12212 away from the negative electrode sheet 13. The average peeling force required to peel the second part 122 from the fourth side 12212 until the second part is peeled from the second end face 134 is 8 N / m-18 N / m, for example, 8 N / m, 9 N / m, 10 N / m, 11 N / m, 12 N / m, 13 N / m, 14 N / m, 15 N / m, 16 N / m, 17 N / m, or 18 N / m. This ensures sufficient adhesion strength between the two separators within the second composite region and between the separator and the second end face of the negative electrode sheet, providing effective constraint and coverage for the edge region of the negative electrode active layer along the first direction. This enhances the interfacial bonding strength between the edge region of the negative electrode active layer and the negative electrode current collector, further reducing or even preventing slippage or lifting of the negative electrode active layer that could puncture the separator during mechanical impact, thus improving battery safety.

[0054] In this invention, the average peeling force required to peel the first part from the third side until the first part is separated from the first end face is obtained by testing using the following method: For example, after discharging the finished battery to 0% SOC, the battery is disassembled in a dry environment with a dew point below -40°C, and the electrode and separator are peeled off layer by layer to obtain a composite sample of separator (including the first composite region) - negative electrode - separator (including the first composite region). The sample is cut into strips 10mm wide and 50mm long. Double-sided tape is used to fix one side of the separator to a rigid plate, and the plate is fixed to a clamp of a tensile testing machine. The free end of the other side of the separator is clamped to another clamp. A 180° peeling test is performed at a constant speed of 300mm / min, and the average force required to peel the first part from the third side until the first part is separated from the first end face is recorded. The peeling force is obtained by dividing the average force by the width from the third side to the first end face, in N / m. It should be noted that, to further ensure the stability and accuracy of the test results, five strip-shaped test samples can be taken for testing, and the peel force test can be performed according to the above method to obtain five sets of values. The average value can be taken to obtain the final result. In this invention, the average peel force required to peel the second part from the fourth side until the second part peels off from the second end face can be obtained by referring to the above method.

[0055] In some embodiments, in the thickness direction of the negative electrode active layer, the negative electrode active layer includes a first negative electrode coating and a second negative electrode coating stacked together, the second negative electrode coating being located between the first negative electrode coating and the negative electrode current collector, the first negative electrode coating including first silicon carbon particles, the first silicon carbon particles including spherical silicon carbon particles with a sphericity of 0.85-1 (e.g., 0.85, 0.86, 0.87, 0.88, 0.89, 0.90, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99 or 1), the second negative electrode coating including second silicon carbon particles, the second silicon carbon particles including blocky silicon carbon particles. The spherical particles in the first negative electrode coating on the surface have regular surfaces without obvious edges or sharp parts. They can effectively prevent particles from piercing the separator during side impacts, further improving the safety of the battery under mechanical impact. At the same time, the blocky silicon-carbon particles have a relatively large specific surface area and a large contact area with the negative electrode current collector. The second negative electrode coating placed at the bottom can enhance the bonding force between the negative electrode active layer and the negative electrode current collector, further reducing the risk of interface peeling and improving the safety of the battery under side mechanical impact conditions.

[0056] In this invention, the sphericity of the first silicon-carbon particle can be measured by the following method: A cross-sectional image of the first negative electrode coating along the thickness direction of the negative electrode sheet is captured using a scanning electron microscope (SEM). Within an arbitrarily selected 100μm × 100μm area, silicon-carbon particles are identified using image analysis software (e.g., ImageJ, NanoMeasurer, Matlab, ParticleMetric, etc.), and the radius r of the equivalent circle representing the projected perimeter of a single silicon-carbon particle is calculated. 1 The radius r of the equivalent circle of the projected area of ​​silicon-carbon particles 2 The sphericity of a single silicon-carbon particle = r 2 / r 1 The sphericity of any 50 silicon carbide particles is statistically analyzed and the arithmetic mean is calculated. This arithmetic mean is the sphericity of the silicon carbide particles. If the number of silicon carbide particles in a single image is less than 50, multiple images are taken until the total number reaches 50.

[0057] In some embodiments, the thickness of the first negative electrode coating is 25μm-35μm, for example, 25μm, 26μm, 27μm, 28μm, 29μm, 30μm, 31μm, 32μm, 33μm, 34μm or 35μm.

[0058] In some embodiments, the thickness of the second negative electrode coating is 15μm-25μm, for example, 15μm, 16μm, 17μm, 18μm, 19μm, 20μm, 21μm, 22μm, 23μm, 24μm or 25μm.

[0059] In some embodiments, the Dv90, Dv50, and Dv10 of the silicon carbide particles satisfy the relationship: 0.3≤(Dv90-Dv10) / Dv50≤1.5, wherein the units of Dv90, Dv50, and Dv10 of the silicon carbide particles are μm. Controlling the Dv90, Dv50, and Dv10 of silicon-carbon particles to satisfy the relationship 0.3≤(Dv90-Dv10) / Dv50≤1.5 ensures a relatively uniform particle size distribution of silicon-carbon particles, avoids particle mixing, and prevents sharp particles from piercing the separator at the edge of the negative electrode active layer, further ensuring the battery's resistance to side mechanical impacts and improving safety. When (Dv90-Dv10) / Dv50 is too large, for example, greater than 1.5, the particle size distribution of silicon-carbon particles is too wide, and silicon-carbon particles of different sizes are mixed, which will affect the consistency of the negative electrode active layer and the uniformity of silicon-carbon particle stacking, increase the risk of sharp particles piercing the separator at the edge of the negative electrode active layer, and is not conducive to further improving battery safety.

[0060] In some embodiments, the Dv90 of the silicon carbide particles is 12μm-20μm, for example, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm or 20μm.

[0061] In some embodiments, the Dv50 of the silicon carbide particles is 6μm-12μm, for example, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm or 12μm.

[0062] In some embodiments, the Dv10 of the silicon carbide particles is 5μm-10μm, for example, 5μm, 6μm, 7μm, 8μm, 9μm or 10μm.

[0063] According to one specific embodiment, the silicon carbide particles have a Dv90 of 12μm-20μm, a Dv50 of 6μm-12μm, and a Dv10 of 5μm-10μm. The Dv90, Dv50, and Dv10 of the silicon carbide particles satisfy the following relationship: 0.3≤(Dv90-Dv10) / Dv50≤1.5.

[0064] In this invention, the Dv10 of the silicon carbide particles refers to the particle size at which the cumulative volumetric particle size distribution percentage of the silicon carbide particles reaches 10% when arranged in ascending order of particle size; the Dv50 of the silicon carbide particles refers to the particle size at which the cumulative volumetric particle size distribution percentage of the silicon carbide particles reaches 50% when arranged in ascending order of particle size; and the Dv90 of the silicon carbide particles refers to the particle size at which the cumulative volumetric particle size distribution percentage of the silicon carbide particles reaches 90% when arranged in ascending order of particle size. In this invention, the Dv10, Dv50, and Dv90 of the silicon carbide particles can be obtained by testing with a particle size analyzer.

[0065] In this invention, when the negative electrode active layer comprises a first negative electrode coating and a second negative electrode coating stacked together, the silicon carbon particles comprise a first silicon carbon particle and a second silicon carbon particle.

[0066] In some embodiments, the negative electrode active material may further include carbon-based particles, which include at least one of graphite particles, hard carbon particles, and soft carbon particles.

[0067] In some embodiments, the negative electrode active layer includes a negative electrode binder, which includes a polyacrylonitrile compound.

[0068] During the charge and discharge process of silicon-carbon systems, silicon-carbon particles exhibit a large volume change rate. In the later stages of cycling, the adhesion of the negative electrode active layer decreases, microcracks accumulate in the coating, and interfacial bonding weakens. When the sides of a stacked battery are subjected to mechanical impact, the edge region of the already deteriorated negative electrode active layer is more prone to slippage and powder shedding. This makes the separator more susceptible to puncture and internal short circuits when the battery is subjected to mechanical impact. In contrast, polyacrylonitrile compounds contain strongly polar cyano groups in their molecular chains, which can form strong hydrogen bonds and van der Waals forces with the surface of silicon-carbon particles. This results in polyacrylonitrile compounds having higher bonding strength and resistance to electrolyte swelling than other aqueous binders. Adding polyacrylonitrile compounds as a binder to the negative electrode active layer can improve the adhesion between silicon-carbon particles, reduce powder shedding, maintain the structural integrity of the negative electrode active layer during cycling, delay the interface degradation of the edge region of the negative electrode active layer, and ensure that the constraint effect of the first composite region on the edge of the negative electrode active layer is maintained throughout the entire battery life cycle. This continuously suppresses the slippage of the negative electrode active layer caused by mechanical impact, reduces the risk of separator puncture, and improves the long-term safety of stacked batteries.

[0069] In some embodiments, the polyacrylonitrile compound in the negative electrode active layer has a weight percentage of 3%-6%, for example, 3%, 3.5%, 4%, 4.5%, 5%, 5.5% or 6%.

[0070] In some embodiments, in addition to polyacrylonitrile compounds, the negative electrode binder may also include one or more of styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVDF), polyurethane, acrylate adhesives, polytetrafluoroethylene (PTFE), lithium polyacrylate (PAALi), polyacrylic acid (PAA), sodium polymethyl cellulose (CMC-Na), and lithium polymethyl cellulose (CMC-Li).

[0071] In some embodiments, the negative electrode active layer further includes a negative electrode conductive agent.

[0072] In some embodiments, the negative electrode conductive agent includes one or more of conductive carbon black, acetylene black, Ketjen black, conductive graphite, graphene, conductive carbon fiber, carbon nanotubes, metal powder, and carbon fiber.

[0073] In some embodiments, the thickness of the copper foil is 6μm-12μm, for example, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, or 12μm. Controlling the copper foil thickness within the range of 6μm-12μm can improve the mechanical stability of the negative electrode current collector, reduce the risk of copper foil breakage, and contribute to the high energy density of the battery. When the copper foil thickness is less than 6μm, the mechanical strength is insufficient, making it prone to breakage during lateral mechanical impacts, increasing the risk of separator puncture, reducing safety, and also leading to decreased cycle stability; when the thickness is greater than 12μm, it reduces the energy density of the battery.

[0074] In some embodiments, the separator includes a substrate layer and a heat-resistant coating located on at least one side surface of the substrate layer. The heat-resistant coating includes heat-resistant particles, the composition of which includes at least one of 1,3,5-triazine-2,4,6-triamine, melamine thiocyanate, melamine cyanurate, and melamine cyanurate. When the separator is thermally bonded to form a first composite region or a second composite region, the heat-resistant particles in the heat-resistant coating can enhance the mechanical strength of the separator edge, complementing the composite region structure and synergistically improving the safety performance of the battery under mechanical impact. Simultaneously, the aforementioned compounds can sublimate and absorb heat at high temperatures, absorbing localized heat within the battery and slowing down the thermal shrinkage process of the separator. In high-silicon-carbon systems, changes in electrode volume under cycling or abnormal operating conditions may lead to localized temperature rises. Separators coated with heat-resistant particles containing the aforementioned compounds exhibit improved heat shrinkage resistance, thereby enhancing the battery's thermal safety performance and ultimately improving its safety under lateral mechanical impact conditions.

[0075] In some embodiments, the thickness of the substrate layer is 3μm-10μm, for example, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, or 10μm. Controlling the thickness of the substrate layer to 3μm-10μm is beneficial to improving the puncture resistance of the separator and further enhancing the safety of the battery under lateral mechanical impact conditions. When the thickness of the substrate layer is less than 3μm, the puncture strength is insufficient; when it is greater than 10μm, the internal resistance increases, deteriorating the rate performance of the battery.

[0076] In some embodiments, the substrate layer comprises at least one of polypropylene, polyethylene, and aramid.

[0077] In some embodiments, the thickness of the single-sided heat-resistant coating is 1μm-5μm, for example, 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, or 5μm. Controlling the thickness of the single-sided heat-resistant coating to 1μm-5μm is beneficial to improving the separator's resistance to heat shrinkage, further reducing the risk of internal short circuits and improving battery safety. When the thickness is less than 1μm, the heat shrinkage resistance is insufficient; when the thickness is greater than 5μm, ion transport is hindered, reducing the battery's rate performance.

[0078] In some embodiments, the separator further includes an adhesive layer located on the surface of the heat-resistant coating and / or the surface of the substrate layer. For example, when the heat-resistant coating is located on one side of the substrate layer, the adhesive layer is located on the surface of the heat-resistant coating and the other side of the substrate layer; when the heat-resistant coating is located on one side of the substrate layer, the adhesive layer is located on the other side of the substrate layer; when the heat-resistant coating is located on both sides of the substrate layer, the adhesive layer is located on the surface of the heat-resistant coating. The adhesive layer on the separator surface can further enhance the adhesion between the separator and the negative electrode active layer, which is beneficial to enhance the constraint and adhesion of the separator to the end face of the negative electrode active layer, suppress the edge lifting of the negative electrode active layer, and further improve the safety of the battery under side mechanical impact conditions.

[0079] In some embodiments, the positive electrode sheet includes a positive current collector and a positive active layer located on at least one side of the surface of the positive current collector.

[0080] In this invention, the positive electrode sheet is a conventional positive electrode sheet in the art. The positive electrode active layer may include a positive electrode active material, a positive electrode conductive agent, and a positive electrode binder. The positive electrode active material may include at least one of lithium cobalt oxide (LCO), nickel cobalt manganese ternary material (NCM), nickel cobalt aluminum ternary material (NCA), nickel cobalt manganese aluminum quaternary material (NCMA), lithium iron phosphate (LFP), lithium manganese phosphate (LMP), lithium vanadium phosphate (LVP), lithium manganese oxide (LMO), lithium nickel oxide, lithium nickel manganese oxide binary material, lithium-rich manganese-based material, and lithium manganese iron phosphate. The positive electrode conductive agent may include one or more of conductive carbon black, carbon nanotubes, conductive graphite, and graphene. The positive electrode binder may include one or more of polyurethane, polyvinylidene fluoride (PVDF), acrylic modified PVDF, polyacrylate polymers, acrylic polymers, polytetrafluoroethylene, polyacrylonitrile, polyimide, styrene-butadiene rubber, and styrene-acrylic rubber.

[0081] In this invention, the electrolyte is a conventional electrolyte in the art, comprising lithium salt, organic solvent, and additives; the organic solvent may include carbonate solvents and carboxylic acid ester solvents, wherein the carbonate solvent includes at least one selected from ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC), and the carboxylic acid ester solvent includes ethyl propionate (EP), propyl propionate (PP), ethyl acetate (EA), and ethyl butyrate (EB); the lithium salt includes lithium hexafluorophosphate (LiPF6) and tetrafluoroboric acid. The additive comprises at least one of lithium (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalate borate (LiDFOB), lithium dioxalate borate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorodioxalate phosphate (LiDFOP), and lithium tetrafluorooxalate phosphate (LiTFOP); the additive comprises at least one of nitrile compounds, fluorocarbonates, fluorocarboxylic acid esters, and sulfur-containing compounds.

[0082] In some instances, the battery is a lithium-ion rechargeable battery.

[0083] The present invention will be described in detail below through embodiments. The embodiments described herein are only a part of the embodiments of the present invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.

[0084] Example 1 (1) Preparation of positive electrode The positive electrode active material (lithium cobalt oxide), positive electrode binder (polyvinylidene fluoride PVDF500), and positive electrode conductive agent (conductive carbon black: carbon nanotubes (weight ratio) = 1:1) were mixed in N-methylpyrrolidone (NMP) solvent at a weight ratio of 96:2:2 and continuously stirred under the action of a stirrer to form a uniform and flowing positive electrode slurry. Subsequently, the positive electrode slurry was coated onto both sides of the positive electrode current collector (aluminum foil), and then dried, rolled, and slit to obtain the desired double-sided positive electrode sheet. Alternatively, the positive electrode slurry was coated onto one side of the positive electrode current collector (aluminum foil), and then dried, rolled, and slit to obtain the desired single-sided positive electrode sheet.

[0085] (2) Preparation of negative electrode The first slurry was obtained by mixing first silicon carbide particles (sphericity 0.97), artificial graphite, negative electrode conductive agent (conductive carbon black: carbon nanotubes (weight ratio) = 1:1), polyacrylonitrile compound, and polyvinylidene fluoride in N-methylpyrrolidone (NMP) solvent at a mass ratio of 53:37:3:5:2 and stirring evenly under vacuum. A double-layer coating die is used to coat the surface of the negative electrode current collector (copper foil) with a second slurry to form a wet film. Then, the first slurry is coated on the wet film to form a stacked second negative electrode coating and a first negative electrode coating. The second negative electrode coating is located between the first negative electrode coating and the negative electrode current collector. After drying, rolling and slitting, a negative electrode sheet is obtained. The thickness of the first negative electrode coating is 28 μm, the thickness of the second negative electrode coating is 20 μm, the Dv90 of the silicon carbon particles is 14 μm, the Dv50 of the silicon carbon particles is 9 μm, the Dv10 of the silicon carbon particles is 6 μm, (Dv90-Dv10) / Dv50=(14-6) / 9=0.89, the tensile strength of the copper foil is 430 MPa, the elongation of the copper foil is 11%, and the thickness of the copper foil is 8 μm.

[0086] (3) Electrolyte preparation In an argon-filled glove box (moisture <1ppm, oxygen <1ppm), the following organic solvents—ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC)—are mixed in a mass ratio of 30:30:40. Then, 1.5% fluoroethylene carbonate, 1% vinylene carbonate, 16% LiPF6, and 3% 1,3,6-hexanetrionitrile (based on the total mass of the electrolyte) are slowly added and stirred until homogeneous to obtain the desired lithium-ion battery electrolyte.

[0087] (4) Preparation of diaphragm A polyethylene film with a substrate layer thickness of 7μm was selected, and a melamine cyanurate heat-resistant coating was coated on the surface of the substrate layer, with a single-sided heat-resistant coating thickness of 2μm. The adhesive layer was PVDF.

[0088] (5) Preparation of composite region and lithium-ion battery The prepared separator is folded in a Z-shape, and the independently cut positive and negative electrode sheets are sandwiched between the separator layers to form a Z-shaped stacked electrode assembly. The single-sided positive electrode sheet is placed on the top and bottom layers. A heating mold is used to locally heat the first and second parts of the separator in the electrode assembly at 140°C for 5 seconds, forming a first composite region and a second composite region. The assembly then undergoes electrolyte injection, vacuum sealing, room temperature settling, and high-temperature formation to obtain the desired lithium-ion battery. The electrode assembly includes a first composite region and a second composite region. The first composite region is formed by bonding at least two first parts located on opposite sides of a single negative electrode sheet in the second direction. The second composite region is formed by bonding at least two second parts located in the second direction. In the first direction, the width of the first composite region is 2 mm, the distance between the first edge and the negative electrode sheet in the first direction is 0.4 mm, and the number of first end faces corresponding to the first composite region is 10 (N). 1 =10), the total number of the first end faces is 10 (M 1 =10), (N 1 / M 1 (10 / 10)×100%=100%, peeling the first part from the third side until the first part is peeled off from the first end face, the average peeling force required is 15N / m, in the first direction, the width of the second composite area is 2mm, in the first direction, the distance between the second side and the negative electrode is 0.4mm, the number of second end faces corresponding to the second composite area is 10 (N 2 =10), the total number of the second end faces is 10 (M 2 =10), (N 2 / M 2 (10 / 10)×100%=100%, peeling the second part from the fourth side until the second part is peeled off from the second end face, the required average peeling force is 15N / m.

[0089] Example 2 This embodiment is based on Embodiment 1, except that the electrode assembly only includes the first composite region, and on the second side surface, the second part at least covers part of the second end face of the negative electrode sheet.

[0090] Example 3 Group This set of examples illustrates the effects of changes in the weight ratio of silicon-carbon particles in the negative electrode active layer.

[0091] Example 3-1 This embodiment is based on Embodiment 1, except that the weight ratio of artificial graphite and / or the weight ratio of the negative electrode conductive agent in the negative electrode active layer is changed so that the weight ratio of silicon carbon particles in the negative electrode active layer is 40%.

[0092] Example 3-2 This embodiment is based on Embodiment 1, except that the weight ratio of artificial graphite and / or the weight ratio of the negative electrode conductive agent in the negative electrode active layer are changed so that the weight ratio of silicon carbon particles in the negative electrode active layer is 20%.

[0093] Example 3-3 This embodiment is based on Embodiment 1, except that the weight ratio of artificial graphite and / or the weight ratio of the negative electrode conductive agent in the negative electrode active layer are changed so that the weight ratio of silicon carbon particles in the negative electrode active layer is 80%.

[0094] Examples 3-4 This embodiment is based on Embodiment 1, except that the weight percentage of artificial graphite and / or the weight percentage of the negative electrode conductive agent in the negative electrode active layer are changed so that the weight percentage of silicon carbon particles in the negative electrode active layer is 85%.

[0095] Example 4 group This set of examples illustrates the effects of changes in characteristics such as the first silicon carbide particles, the second silicon carbide particles, the thickness of the first negative electrode coating, the thickness of the second negative electrode coating, (Dv90-Dv10) / Dv50, and the weight percentage of polyacrylonitrile compounds.

[0096] This embodiment group is based on Embodiment 1, except that the characteristics such as the first silicon carbon particles, the second silicon carbon particles, the thickness of the first negative electrode coating, the thickness of the second negative electrode coating, (Dv90-Dv10) / Dv50, and the weight ratio of polyacrylonitrile compounds are changed, as detailed in Table 1.

[0097] Table 1 “ "" indicates that it is the same as in Example 1, and " / " indicates that the data does not exist here.

[0098] Example 5 group This set of examples illustrates the effects of changes in the tensile strength and / or elongation of the copper foil.

[0099] This embodiment group is based on Embodiment 1, except that the tensile strength and / or elongation of the copper foil are changed by adjusting the electrolysis process parameters and / or heat treatment conditions, as detailed in Table 2.

[0100] Table 2 Example 6 group This set of embodiments is used to illustrate the effects that occur when the width of the first composite region and / or the width of the second composite region changes in the first direction.

[0101] This embodiment group is based on Embodiment 1, except that the width of the first composite region and / or the width of the second composite region are changed in the first direction, as detailed in Table 3.

[0102] Table 3 Example 7 group This set of embodiments is used to illustrate the effects that occur when the distance between the first side and the negative electrode in the first direction and / or the distance between the second side and the negative electrode in the first direction changes.

[0103] This embodiment is based on Embodiment 1, except that the distance between the first side and the negative electrode in the first direction and / or the distance between the second side and the negative electrode in the first direction are changed, as detailed in Table 4.

[0104] Table 4 Example 8 group This set of embodiments is used to illustrate the effects of changes in the average peel force required when peeling the first part from the third side to the first end face and / or the average peel force required when peeling the second part from the fourth side to the second end face.

[0105] This embodiment group is carried out with reference to Embodiment 1. The difference is that by changing the heating temperature and / or heating time, the average peeling force required to peel the first part from the third side to the first end face and / or the average peeling force required to peel the second part from the fourth side to the second end face are changed. See Table 5 for details.

[0106] Table 5 Example 9 group This set of examples is used to illustrate when (N) 1 / M 1 )×100% and / or (N 2 / M 2 The effect of changing )×100%.

[0107] This embodiment is based on Embodiment 1, except that the number of bonded diaphragm layers is changed so that (N) 1 / M 1 )×100% and / or (N 2 / M 2 The percentage changes by 100%, see Table 6 for details.

[0108] Table 6 Example 10 group This set of examples illustrates the effects of changes in at least one of the following: the thickness of the substrate layer, the thickness of the one-sided heat-resistant coating, and the composition of the heat-resistant particles.

[0109] Example 10-1 This embodiment is based on Embodiment 1, except that the thickness of the substrate layer is 3μm and the thickness of the heat-resistant coating on one side is 1μm.

[0110] Example 10-2 This embodiment is based on Embodiment 1, except that the thickness of the substrate layer is 10 μm and the thickness of the heat-resistant coating on one side is 5 μm.

[0111] Example 10-3 This embodiment is based on Example 1, except that the heat-resistant particles are composed of melamine trithiocyanate.

[0112] Example 10-4 This embodiment is based on Embodiment 1, except that the heat-resistant particles are composed of boehmite.

[0113] Example 11 group This set of examples illustrates the impact of a change in battery type.

[0114] Example 11-1 This embodiment is based on Embodiment 1, except that in the lithium-ion battery preparation, the prepared positive electrode sheet and negative electrode sheet are first die-cut, then the positive electrode sheet and separator are bagged and cut, and then alternately stacked with the negative electrode sheet to obtain an E-type stacked electrode assembly. The electrode assembly includes a first composite region and a second composite region.

[0115] Example 11-2 This embodiment is based on Embodiment 1, except that in the lithium-ion battery preparation, the prepared positive electrode sheet and negative electrode sheet are first die-cut, then the positive electrode sheet and separator are bagged and cut, and then alternately stacked with the negative electrode sheet to obtain an E-type stacked electrode assembly. The electrode assembly only includes the first composite region.

[0116] Comparative Example 3 This embodiment is based on Embodiment 1, except that the electrode assembly does not include the first composite region or the second composite region.

[0117] Test case The batteries prepared in the examples and comparative examples were subjected to the following performance tests, and the test results are shown in Table 7: (1) Side mechanical impact pass rate: A fully charged battery cell is fixed on the test platform with the first surface of the electrode assembly facing upwards to prevent movement of the battery cell during the impact. An impactor is dropped from a height of 1.5m onto the side region of the first surface of the electrode assembly along the first direction, including the composite region. The impact location is the middle region of the electrode assembly along the third direction (e.g., Figure 2 (As shown in C and / or D in the diagram), for example, when the electrode assembly includes only the first composite region, the impact location is... Figure 2 In the context of C, when the electrode assembly includes a first composite region and a second composite region, the impact location is... Figure 2 For C or D in the test, after the test, observe whether the individual battery cells show signs of smoke, fire, or explosion, and determine whether an internal short circuit has occurred by monitoring the voltage. If any of the following occurs, the battery is considered to have failed: smoke, fire, explosion, or internal short circuit. If none of these occur, the battery is considered to have passed: if 20 batteries are tested, and X batteries pass, the pass rate is X / 20.

[0118] (2) Capacity retention rate during 25℃ cycling: At 25℃±2℃, the battery was charged at a constant current and constant voltage of 0.7C to the upper limit voltage of 4.53V, then cut off at 0.05C, and then discharged at a constant current of 0.2C to the lower limit voltage of 3V. The initial discharge capacity is denoted as C. 1 After 10 minutes of rest, the cycle is as follows: 3C constant current / constant voltage charging to 4.25V, cut off at 2C, then 2C constant current / constant voltage charging to 4.48V, cut off at 1.5C, then 1.5C constant current / constant voltage charging to the upper limit voltage of 4.53V, cut off at 0.18C, rest for 5 minutes, and then discharge at 0.7C to the lower limit voltage of 3V. After 500 cycles, 0.7C constant current / constant voltage charging is performed to the upper limit voltage of 4.53V, cut off at 0.05C, and then 0.2C constant current discharge is performed to the lower limit voltage of 3V. The final discharge capacity is recorded as C. 2 Capacity retention rate = (C 2 / C 1 )×100%.

[0119] (3) Ratio performance: At 25±3℃, after standing for 5 minutes, discharge at 1.1A to the cutoff voltage of 2.5V, after standing for 5 minutes, fully charge at 0.5C standard charging to 4.56V with a cutoff current of 0.02C, after standing for 30 minutes, discharge at 2C rate to the cutoff voltage of 2.5V, and record the discharge capacity as Q. 1 After resting for 5 minutes, it is fully charged to 4.56V using a standard 0.5C charging method, with a cutoff current of 0.02C. After resting for 30 minutes, it is discharged at 2C to a cutoff voltage of 2.5V. The discharge capacity is recorded as Q. 2 Discharge rate performance = (Q 2 / Q 1 )×100%, test 3 batteries, take the average value as the final result.

[0120] (4) Volumetric energy density: The battery was left to stand for 1 hour at (25±2)℃. It was then charged at a constant current of 0.5C to 4.53V, and then charged at a constant voltage of 4.53V to a current of 0.05C, and left to stand for 10 minutes. Next, it was discharged at a constant current of 0.2C to 3V and left to stand for 10 minutes. The discharge capacity was recorded as q, the average discharge plateau voltage as v, the lithium-ion battery thickness as h, the lithium-ion battery length (dimension in the second direction) as y, the lithium-ion battery width (dimension in the first direction) as z, and the volumetric energy density as (q×v) / (h×y×z), in Wh / L.

[0121] Table 7 The " / " indicates that the corresponding embodiment did not perform this test, so there is no data here.

[0122] As can be seen from Table 7, by comparing the comparative examples and the embodiments, the embodiments show improved side mechanical impact pass rate and room temperature cycle capacity retention rate, while ensuring higher rate performance and volumetric energy density. This indicates that by controlling the tensile strength and elongation of the portion of the separator extending beyond the negative electrode sheet, including the first composite region and the copper foil, the slippage and warping of the negative electrode active layer can be improved, the puncture of the separator can be reduced, and the problems of short circuits easily occurring on the side of the silicon-carbon stacked battery along the width direction under mechanical impact can be improved. This improves the safety of the side of the stacked battery under mechanical impact and the cycle capacity retention rate of the battery, while effectively maintaining the volumetric energy density and rate performance.

[0123] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A battery, characterized in that, The battery includes a stacked electrode assembly, which includes a positive electrode, a separator, and a negative electrode. The negative electrode includes a negative current collector and a negative active layer located on at least one side of the negative current collector. The negative active layer includes a negative active material, which includes silicon carbon particles. The negative current collector includes copper foil with a tensile strength of 300 MPa-700 MPa and an elongation of 3%-15%. The electrode assembly includes a first side surface and a second side surface disposed opposite to each other along a first direction. In the first direction, the separator includes a first portion and a second portion extending beyond the negative electrode sheet. The first portion is located on the side closer to the first side surface, and the second portion is located on the side away from the first side surface. The first portion includes a first composite region, which is formed by bonding two first portions located on opposite sides of a single negative electrode sheet in a second direction.

2. The battery according to claim 1, wherein, The elongation of the copper foil is 10%-13%; And / or, the silicon-carbon particles account for 20%-80% by weight in the negative electrode active layer, preferably 40%-80%; And / or, in the first direction, the width of the first composite region is 0.8mm-2.5mm; And / or, the first composite region includes a first side close to the negative electrode, wherein in the first direction, the distance between the first side and the negative electrode is greater than or equal to 0.2 mm; And / or, the negative electrode active layer includes a negative electrode binder, the negative electrode binder including a polyacrylonitrile compound; preferably, in the negative electrode active layer, the weight percentage of the polyacrylonitrile compound is 3%-6%.

3. The battery according to claim 1, wherein, The negative electrode has a first end face and a second end face at both ends in a first direction. The first end face is located on one side of the first side surface, and the second end face is located on one side of the second side surface. The positive electrode has a third end face and a fourth end face at both ends in a first direction. The third end face is located on one side of the first side surface, and the fourth end face is located on one side of the second side surface. The second part at least covers a portion of the second end face of the negative electrode and / or the second part at least covers a portion of the fourth end face of the positive electrode.

4. The battery according to claim 1, wherein, The second part includes a second composite region, which is formed by bonding at least two second parts located in the second direction; Preferably, in the first direction, the width of the second composite region is 0.8mm-2.5mm; Preferably, the second composite region includes a second side close to the negative electrode sheet in the first direction, and the distance between the second side and the negative electrode sheet in the first direction is greater than or equal to 0.2 mm.

5. The battery according to claim 4, wherein, The negative electrode has a first end face and a second end face at both ends in a first direction. The first end face is located on one side of the first side surface, and the second end face is located on one side of the second side surface. On the first side surface, the number of first end faces corresponding to the first composite region is N. 1 The total number of the first end faces is M. 1 N 1 and M 1 Satisfying 20% ​​≤ (N) 1 / M 1 )×100%≤100%, preferably, the electrode assembly includes a first surface and a second surface disposed opposite to each other along the second direction, the first composite region being close to the first surface along the second direction, and / or, the first composite region being close to the second surface along the second direction; And / or, on the second side surface, the number of second end faces corresponding to the second composite region is N. 2 The total number of the second end faces is M. 2 N 2 and M 2 Satisfying 20% ​​≤ (N) 2 / M 2 )×100%≤100%; Preferably, the electrode assembly includes a first surface and a second surface disposed opposite to each other along the second direction, the second composite region being close to the first surface along the second direction, and / or, the second composite region being close to the second surface along the second direction.

6. The battery according to claim 4, wherein, The negative electrode sheet has a first end face and a second end face at both ends in a first direction. The first end face is located on one side of the first side surface, and the second end face is located on one side of the second side surface. The first composite region includes a third side away from the negative electrode sheet. The first part is peeled off from the third side until the first part is peeled off from the first end face. The average peeling force required is 8N / m-18N / m. And / or, the second composite region includes a fourth side away from the negative electrode sheet, from which the second part is peeled off until the second part is peeled off from the second end face, the required average peeling force being 8N / m-18N / m.

7. The battery according to claim 1, wherein, In the thickness direction of the negative electrode active layer, the negative electrode active layer includes a first negative electrode coating and a second negative electrode coating stacked together. The second negative electrode coating is located between the first negative electrode coating and the negative electrode current collector. The first negative electrode coating includes first silicon carbon particles, which are spherical silicon carbon particles with a sphericity of 0.85-1. The second negative electrode coating includes second silicon carbon particles, which are blocky silicon carbon particles. Preferably, the thickness of the first negative electrode coating is 25μm-35μm; Preferably, the thickness of the second negative electrode coating is 15μm-25μm.

8. The battery according to claim 1, wherein, The diaphragm includes a substrate layer and a heat-resistant coating located on at least one side of the substrate layer. The heat-resistant coating includes heat-resistant particles, and the heat-resistant particles are composed of at least one of 1,3,5-triazine-2,4,6-triamine, melamine thiocyanate, melamine cyanurate, and melamine cyanurate. Preferably, the thickness of the substrate layer is 3μm-10μm, and / or the thickness of the single-sided heat-resistant coating is 1μm-5μm.

9. The battery according to claim 1, wherein, The Dv90, Dv50, and Dv10 of the silicon carbide particles satisfy the following relationship: 0.3≤(Dv90-Dv10) / Dv50≤1.5, where the units of Dv90, Dv50, and Dv10 of the silicon carbide particles are μm. And / or, the Dv90 of the silicon carbide particles is 12μm-20μm; And / or, the Dv50 of the silicon carbide particles is 6μm-12μm; And / or, the Dv10 of the silicon-carbon particles is 5μm-10μm.

10. The battery according to any one of claims 1-9, wherein, The thickness of the copper foil is 6μm-12μm.